PENGARUH PENGALAMAN AUDIT, BEBAN KERJA, TASK SPECIFIC KNOWLEDGE, TIPE KEPRIBADIAN TERHADAP PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN (Studi Kasus Kantor Akuntan Publik Kota Palembang) - Kusumawaty, Mia; Betri, Betri (Balance : Jurnal Akuntansi dan Bisnis, 2019)
The formulation of this research is how influence of Audit Experience, Workload, Task Specific Knowledge, Personality Types on the detection of Financial Report Fraud case study at Public Accounting Firm Palembang. The purpose is to know, get empirical evidence and analyze Audit Experience, Workload, Task Specific Knowledge, Personality Types on Financial Report Fraud. This study includes Associative research. The population used in this study is the Auditor who works in the Public Accounting Firm Palembang. Sample in this research counted 37 Respondents. Methods Data collection used in this study is a questionnaire. Hypothetical test used is multiple linear regression.   The results of this study show Partial Audit Experience has a positive effect on Fraud Financial Statements, Workload positively affect the Financial Report Fraud, Task Specific Knowledge positively affect the Fraud Financial Statements, Personality Types positively affect The Financial Report Fraud. Simultaneously Audit Experience, Workload, Task Specific Knowledge, Personality Types positively influence to Financial Report Fraud.